PEMBERIAN MAHAR DI ERA DIGITAL : PANDANGAN EKONOMI DAN PERSFEKTIF AL-QUR’AN - Hasiah Hasiah; Rahmi rahmi; Sawaluddin Siregar; Shafra shafra; Rahmawati wati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research explores the economic persfective and Quranic persfective on the practice of giving a dowry in the context of technology and digitization. The giving of dowry, as an integral part of marriage in Islam, undergoes significant transformation in the digital era. By integrating Islamic economic approaches and Quranic interpretations, this research aims to understand the impact of technological changes on the value and meaning of dowry, as well as how Islamic views adapt to digital realities. This study utilitizes a literature analysis method to investigate economic concepts in dowry giving and explore Quranic verses related to dowry, in line with technological developments. The findings of this research reflect the role of dowry in strengthening the family economy and involving Islamic values in a modern context. Digitization implicates the dowry-giving process, including changes in behavior patterns and the emergence of economic values. Technological developments suggest that dowry-giving reflect traditional and spiritual values, which remain relevant in the gace of ever-changing challenges.